PERTUMBUHAN SPORA Gracillaria sp PADA SALINITAS BERBEDA - Hasim Hasim; Mulis Mulis; Basman B Indak (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2019)
The demand for Gracillaria commodities continues to increase for food, medicines, and beauty ingredients. These conditions encourage the cultivation of this commodity continues to proliferate. Because of that, availability of Gracillaria sp seeds is available both in quantity and quality. One effort that can be done in handling the Gracillaria sp spores through environmental engineering. One such factor is fisheries salinity. The difference in salinity supports the increase in Gracillaria spores so that it affects spore growth. The aim of the study was to study the growth of Gracillaria spores cultured on different salinity media. The method used is a laboratory experiment method with a completely randomized trial design (CRD) with forty salinity preparations (23 ppt, 26 ppt, 29 ppt, and 32 ppt) and is repeated three times. The resulting data were then analyzed by analysis of variance. The results showed the highest spore growth at 23 ppt salinity with the number of spores (560.9 Ind / cm2), then 26 ppt salinity (438.8 Ind / cm2), then 32 ppt salinity (429.9 Ind / cm2) and low in salinity 29 with the number of spores (277.8 Ind / cm2). Fingerprint analysis showed that each evaluation results were not significantly different.